PERILAKU ANAK BERKEBUTUHAN KHUSUS GANGGUAN AUTISME DI SLB NEGERI SEMARANG TAHUN 2014 - Widiastuti, Diah (BELIA: Early Childhood Education Papers, 2014)
Perilaku merupakan salah satu hal yang melekat pada diri manusia, respon terhadap stimulus, segala tindakan yang dilakukan, berbagai gerakan yang ada dalam diri kita baik disengaja maupun tidak.  Perilaku anak autisme tentu berbeda dengan anak normal biasa, karena autisme merupakan gangguan dimana anak sulit dalam berinteraksi dengan orang lain. Tujuan penelitian ini untuk mengetahui perilaku anak berkebutuhan khusus dengan gangguan autisme di SLB Negeri Semarang tahun 2014, mengetahui hubungan sosial dan komunikasi di lingkungan sekitarnya serta mengetahui intervensi terhadap perilaku anak dengan gangguan autisme. Jenis penelitian yang digunakan adalah penelitian kualitatif, teknik pengumpulan data yang digunakan teknik observasi, wawancara, dan dokumentasi.  Informan penelitian adalah   ibu dari anak autisme, guru dan terapis di SLB Negeri Semarang. Analisis datanya menggunakan reduksi data, penyajian data, kesimpulan dan verifikasi. Keabsahan data penelitian menggunakan teknik triangulasi. Hasil penelitian menunjukkan secara keseluruhan, perilaku mereka menampakkan perbedaan, DNA tergolong autisme ringan menunjukkan perilaku yang berkekurangan (deficient) dan ditunjukkan dengan ekolalia (pengulangan kata), sedangkan BGS yang tergolong kategori berat lebih menunjukkan perilaku yang berlebihan (excessive) seperti mengamuk, menjambak, berteriak. Hubungan sosial dan komunikasi kedua subjek juga sama seperti anak autis lainnya yakni mereka masih mengalami kesulitan berinteraksi dengan orang lain.  Seiring dengan perbedaan perilaku mereka, maka intervensi terhadap keduanya juga berbeda. Intervensi yang diberikan kepada DNA cenderung melalui ucapan, dengan cara penekanan terhadap suara yang jelas dan lantang seperti akan marah.  Sedangkan BGS yang tergolong kategori berat, intervensi yang diberikan kepadanya cenderung melalui tindakan fisik, karena perilakunya yang berlebihan seperti agresif, dan melukai orang lain, perlakuan melalui ucapan dengan penekanan tidak akan berpengaruh terhadap dirinya.The research problems are include (1)  How is the cooperative model type talking stick which is helped multimedia quiz creator to improve the senior high school students’ folklore attentive skill. (2) how is the principles of cooperative model type talking stick development which is helped by multimedia quiz creator to improve the  senior high school students’ folklore attentive skill. This research uses research and development design (R&D), this research developes model which  have been exist that is cooperative model type talking stick into cooperative model type talking stick which is helped by multimedia quiz creator. The results of the researches are : (1) the teacher and students’ need toward to cooperative model type talking stick which is helped by multimedia quiz creator. (2) cooperative model type talking stick priciples are (a) innovative learning strategy, (b) innovative learning media, (c) assessment. Behavior is one of the things that attach to human beings, response to stimulus, all the things that is done, our various possible movement whether deliberate or not. Behavior of autism children is clearly different to normal children, since autism is a disorder in which the children get difficulties in communicating with the others. The objectives of this study are to observe the behavior of the children with special needs of autism disorder in Semarang State Outstanding School in the year 2014, to understand the communication and social relationship in their surroundings, and to know the intervention of children’s behavior with autism disorder. The researcher used qualitative method, is that in collecting the data the researcher did observation, interview, and documentation technique. The informants were the teacher, mother, and the therapist of autism children in Semarang State Outstanding School. Meanwhile, in term of analysis researcher used data reduction, data presentation, conclusion, and verification. The data legality was defined by triangulation technique. The result of the study shows that both subjects of DNA and BGS are normal birth and do not show any differences of growth until their age entering 2-3 years old. Over all, their behavior shows contradiction, the DNA of mild autism shows deficient behavior and it is showed by ekolalia (word repeating), while BGS in serious category showing more excessive behavior such as rage violently, tufting, and screaming. Communication and social relationship of that two subjects also the same as the other autism children, they still get difficulties in interacting with the others. In a row with their behavior, the intervention to them is also different. Intervention that is given to DNA tends to by words, with strong stressing of clear voice and piercing. Whereas BGS with serious category, intervention that is given tends to physical treatment because of their excessive behavior, such as aggressive and hurting someone else, treating by words with stressing will not affect to themselves.